Perjanjian Pokok dan Perjanjian Hak Tanggungan dikaitkan dengan Asas Pelengkap - Seroja, Triana Dewi; Fitri, Winda (Journal of Law and Policy Transformation, 2019)
Agreements for mortgages and complementary principles are two important legal issues in the Underwriting Rights Law. As a complement to the existence of an agreement on mortgages, it depends on the main agreement. Hence, its existence must be preceded by a principal agreement.This research uses the legal normative approach. It is a research method conducted by analyzing secondary data and utilizing a analytical descriptive. Based on the results of the analysis, it was found that the Underwriting Agreement preceded by the Principal Agreement could not be legally justified. This is Underwriting Rights are esablished or only have power, if the debt guaranteed by Underwriting Rights already exists. Unlike the case with the burden of mortgages that have been granted in the first credit agreement. It can also be charged to the next credit agreement that will exist in the future. Therefore, the Underwriting Law can be justified because it is in accordance with the complementary principle.